Pediatric Pulmonary Hypertension: Guidelines From the American Heart Association and American Thoracic Society. Issue 21 (24th November 2015) - Abman, Steven H.; Hansmann, Georg; Archer, Stephen L.; Ivy, D. Dunbar; Adatia, Ian; Chung, Wendy K.; Hanna, Brian D.; Rosenzweig, Erika B.; Raj, J. Usha; Cornfield, David; Stenmark, Kurt R.; Steinhorn, Robin; et al.
Abstract : Pulmonary hypertension is associated with diverse cardiac, pulmonary, and systemic diseases in neonates, infants, and older children and contributes to significant morbidity and mortality. However, current approaches to caring for pediatric patients with pulmonary hypertension have been limited by the lack of consensus guidelines from experts in the field. In a joint effort from the American Heart Association and American Thoracic Society, a panel of experienced clinicians and clinician-scientists was assembled to review the current literature and to make recommendations on the diagnosis, evaluation, and treatment of pediatric pulmonary hypertension. This publication presents the results of extensive literature reviews, discussions, and formal scoring of recommendations for the care of children with pulmonary hypertension. Abstract : Supplemental Digital Content is available in the text.